SOCIALIZATION OF COMMUNITY RIGHTS TO HEALTH CARE SERVICES AT SERING ATAS - Asri Reni Handayani; Nur Arifatus Sholihah; Ana Lestari (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2021)
Achieving good health is one of the needs that must be met by every humans being. In addition to primary, secondary, and tertiary needs, the realization of health is the main key for humans to carry out all activities and ultimately fulfill the three elements of human needs. Policymakers still do not regard health as a primary need and a valuable investment in development. It's time to consider health issues an important factor and a worthwhile investment. Its implementation is based on a new paradigm commonly known as the healthy paradigm, wich health paradigm that prioritizes promotive and preventive efforts without neglecting curative and rehabilitative efforts. Therefore, every community has the right to live in a good and healthy environment. So all citizens of the Republic of Indonesia have the right to access health care services. However, people still assume that medical services are only used if they are sick or have symptoms of illness. The purpose of this community service is to increase and develop public knowledge about the community’s right to health care services. The material was delivered using the lecture method at Dusun Sering Atas. The planned result is to increase public knowledge and awareness of the importance of the community's right to health care services. The result achieved is an increased in general understanding and awareness of the right to health care services.